Akuisisi Bahasa Arab Pada Tataran Gramatika dan Rasa Bahasa Bagi Pembelajar Non Arab - Mukhlis Anshari (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2018)
Acquisition of Arabic language at the level of language sense that the acquisition of language that has reached the stage of intact understanding of the context of the meaning of each word and phrase delivered by the native speakers both verbally and non verbally. Verbally, it means that a learner understands what the native speakers say. While the meaning of non vebal, the language conveyed by the native speakers in the form of papers, in the form of books or literary manuscripts